The Vanishing Sector. A Case Study on Private Higher Education Institutions in Poland - Geryk, Marcin (Contemporary organisation and management. Challenges and trends, 2020)
The main aim of this paper is to introduce the publication of a research-based monograph on private higher education institutions in Poland. A brief presentation of data obtained during a cross-sectional study carried out in 2015–2019 shows the challenges that private universities in Poland face. Demographic turmoil is resulting in shrinking funds, and the diminishing number of students is a threat to the existence of some institutions, mostly those which are smaller ones or with a lower number of programmes and students enrolled.